2009
DOI: 10.1097/eja.0b013e32831c8939
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic but not lumbar epidural anaesthesia increases liver blood flow after major abdominal surgery

Abstract: Liver perfusion was increased with thoracic but not lumbar EAA after major abdominal surgery in most patients. PDR(ICG) allows assessment of individual changes of liver blood flow due to therapeutic intervention, for example, EAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 21 publications
0
31
2
Order By: Relevance
“…This result leads to the consideration that similar blood flow and hemodynamic data are obtained in humans as a result of similar sympatholysis. However, Kortgen et al [3] demonstrated, contrary to our study, that TEA increased hepatic perfusion in most patients after major abdominal surgery. Meierhenrich et al [11] reported that TEA along with transesophageal echocardiography significantly decreased hepatic venous blood flow.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result leads to the consideration that similar blood flow and hemodynamic data are obtained in humans as a result of similar sympatholysis. However, Kortgen et al [3] demonstrated, contrary to our study, that TEA increased hepatic perfusion in most patients after major abdominal surgery. Meierhenrich et al [11] reported that TEA along with transesophageal echocardiography significantly decreased hepatic venous blood flow.…”
Section: Discussioncontrasting
confidence: 99%
“…Epidural anesthesia and analgesia are shown to be effective in reducing perioperative risks, such as intraoperative blood flow and thromboembolic events, and improving postoperative respiration, cardiovascular, and intestinal function and modified immune function. In addition, epidural anesthesia is considered to increase organ perfusion in the splenic area by means of sympathetic blockage [3].…”
mentioning
confidence: 99%
“…Spackman et al [26] evaluated the effects of TEA on a group of critically ill patients with surgically treated peritonitis, they found better pHi and PCO2 gap in patients treated with epidural infusion of bupivacaine. Kortgen et al [27] found an increase in liver blood flow measured with PDRICG in patients undergoing major abdominal surgery and treated with thoracic epidural anesthesia in addition to general anesthesia. This finding couldn't be replicated by using lumbar epidural anesthesia and general anesthesia as anesthetic technique.…”
Section: Rabbits Hoganmentioning
confidence: 99%
“…The six studies using surrogate hemodynamic parameters had conflicting results. Tanaka et al [23] used PDRicg as indirect measure of hepatic blood [7] Hogan et al [8] Sielenkämper et al [10] Adolphs et al [12] Adolphs et al [11] Schwarte et al [15] Kosugi et al [9] Freise et al [13] Daudel et al [14] Bachmann et al [16] Tanaka et al [23] Väisänen et al [25] Spackman et al [26] Gould et al [20] Michelet et al [22] Kortgen et al [27] Meierhenrich et al [21] Trepenaitis et al [24] Treatment Meissner et al [4] Ai et al [6] Vagts et al [5] Shäper et al [3] Freise et al [17] Freise et al [18] Treatment allocation Siniscalchi A et al . Thoracic epidural anesthesia flow, finding that TEA reduced blood flow to the liver, fluid resuscitation alone could not reverse this effect but had to be associated with dopamine infusion.…”
Section: Rabbits Hoganmentioning
confidence: 99%
“…Improved gastrointestinal blood flow and motility are clear in animals, and in clinical studies epidurals have been shown to improve recovery after major abdominal surgery. Liver perfusion increases with thoracic but not lumbar epidural analgesia after major abdominal surgery in most patients (Kortgen 2009). However, its use alone cannot prevent postoperative morbidity and mortality (Clemente 2008).…”
Section: Physiological Reactions To Surgerymentioning
confidence: 99%